Are the taxpayers' rights adequately protected in Malaysia? / Kok Fie See - Kok, Fie See (2011)
Income tax is the main source of revenue income for the Malaysian Government. There is an inherent danger of abuse in the current income tax administration system -- the administrative body for direct taxes (including income tax), i.e., the Inland Revenue Board Malaysia is part of the Ministry of Finance of Malaysia. Further the independence of the Special Commissioners of Income Tax ("SCIT") in disposing of the appeals of the taxpayers is tainted by the fact that the SCIT are officers of the Treasury of Malaysia. In limited circumstances, the taxpayers are allowed to circumvent the normal appeal procedure before the SCIT under the Income Tax Act 1967 ("IT A") and to apply for judicial review instead to the High Court against the decision of the Director General of Inland Revenue. The appeal procedures do not preserve the rights of the taxpayers pending the determination of the appeals by the SCIT or the High Court. The taxpayers are still required to pay the taxes in dispute and have limited defences in the civil recovery actions for taxes due and payable to the Malaysian Government. Reform of income tax administration system is of utmost importance with a view of improving the level of protection of the taxpayers' rights in Malaysia.